2011
DOI: 10.1007/s00264-011-1327-2
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Relationship of serum IL-6, C-reactive protein, erythrocyte sedimentation rate, and knee skin temperature after total knee arthroplasty: a prospective study

Abstract: We regret that the value of serum CRP was reported incorrectly. Serum CRP levels were reported incorrectly to be 10 times higher than their true value. The value of serum CRP in osteoarthritis patients following total knee arthroplasty should have been reported in milligrams per litre (mg/l), instead of milligrams per decilitre (mg/dl) for the whole article. The authors apologise for this error.The online version of the original article can be found at http://dx.doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…IL-6 levels peak within 6–12 hours after major surgery and then return to baseline levels within 48–72 postoperative hours [ 31 – 35 ]. We also found that IL-6 levels rapidly declined by the third postoperative day, which is consistent with other reports [ 36 39 ]. However, IL-6 in our triclosan group fell to lower than baseline levels at 2 weeks, 4 weeks, and 3 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…IL-6 levels peak within 6–12 hours after major surgery and then return to baseline levels within 48–72 postoperative hours [ 31 – 35 ]. We also found that IL-6 levels rapidly declined by the third postoperative day, which is consistent with other reports [ 36 39 ]. However, IL-6 in our triclosan group fell to lower than baseline levels at 2 weeks, 4 weeks, and 3 months.…”
Section: Discussionsupporting
confidence: 93%
“…There were no significant differences in the mean global or regional surface temperature of the operated knee between the triclosan and control groups during the 6-month follow-up. As with the analysis of early postoperative subclinical inflammation in primary TKA [ 36 , 39 , 43 ], surface temperature changes mirrored the levels of serologic inflammatory markers. It may also have been confounded and masked by the abovementioned factors.…”
Section: Discussionmentioning
confidence: 88%